ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEBIJAKAN HARGA TERHADAP LOYALITAS KONSUMEN (Studi Kasus: PT. GDI - Fuad Dwi Hanggara; Arrazy Elba Ridha; Aulia Agung Dermawan (Universitas Putera Batam, 2022)
Loyalty is something that cannot be bought with money, but can be obtained if you try to increase trust in customers. This study aims to analyze the effect of service quality variables and price policy on consumer loyalty variables. This research was conducted by dividing the questionnaire as an instrument. Customers today are faced with a number of alternative ways when choosing a store that suits their tastes. But every company must also be able to compete by setting itself up for changes and developments that exist, both from outside and inside so that a company can maintain this competition. The method of analysis was carried out by means of quantitative descriptive methods through survey techniques using questionnaires. The population used is 100 respondents, and the number of samples taken is 96 respondents. Data analysis was carried out using multiple linear regression analysis. The data quality test in this study uses validity and reliability tests, the classical assumption test in this study uses the normality test, multicollinearity test, and heteroscedasticity test, and the effect test uses multiple linear regression analysis and analysis of the coefficient of determination (R2), while hypothesis testing in this study uses t-test and F test using IBM SPSS Statistics version 25 program.